‘The way we judge’ Observers’ assessing of elder care decisions of adult children who had been abused by the parents and the ultimate attribution error - Ammann, Claudia G. (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2019)
In this essay I want to concentrate on observers’ baseline assumptions on how we should be, or should have become in order to be accounted as morally ‘good.’ I will point out the significance for adult children who decided to not care for their elder parents. In three selected studies I show that observers, in trying to explain the decisions of others, or their moral development, respectively moral standing, misjudge or ignore their own implicit baseline assumptions. These assumptions are symptomatic of an implic¬it belief in all of us that wishes to see that ’good begets good’ for most of us, and infers, thereafter, that ‘bad begets bad’ for some who would show ‘no good.’ It is this implicit belief that guides the observers to make assumptions about the morally doubtful upbringing of a person, or their negative behavior that they wish to explain by flaws in the person’s personality. This biased belief says “it is this way, and only this way”, but, in fact, one cannot be certain about it. The baseline assumptions that observers bring along are basically the biased observer’s points of view which can be explained with the ultimate attribution error.
Keywords: elder care; child abuse; dilemmatic moral decisions; an ultimate attribution error; care ethics